Interviews in the history of linguistics Volume I - McElvenny, James (Language Science Press, 2022)
This volume brings together transcripts of ten interviews from the podcast series History and Philosophy of the Language Sciences, covering topics in the history of modern European linguistics from the beginning of the nineteenth century to the mid-twentieth century. The transcripts have been reviewed and edited for clarity and completeness.